The frequency effects on fatigue threshold of PVC-M and PVC-U in air and water medium - Samat, Noorasikin; Whittle, Alan; Hoffman, Mark (Trans Tech Publications Ltd., Switzerland, 1998)
The cyclic fatigue threshold value (Kth) of PVC materials with (PVC-M) and without PVC-U) impact modifier was determined and compared in air and water environments. The PVCM specimens contain 6 pphr of chlorinated polyethylene (CPE) impact modifier. The testing was undertaken at a stress ratio of R=0.1 and fatigue threshold was evaluated at 3 different frequencies:1Hz, 7Hz and 20Hz. Frequency noticeably affected the fatigue threshold value; regardless of the testing environment; at low frequency the fatigue threshold of PVC-M was below PVC-U, however,this difference gradually decreased with increasing frequency as Kth of PVC-M increased but Kth of PVC-U remained constant. This trend was accelerated in water where a higher of fatigue threshold, Kth, was also observed. A lower fatigue threshold of PVC-M than PVC-U is associated with the presence of CPE particles. The absorption of water into the PVC matrix was evident with the formation of nodular structures observed on the fracture surface. The presence of the nodular structures (at regions close to the threshold) has retarded the fibrillation of crazes, which then blunted the crack propagation.